PENGARUH PENGEMBANGAN KARIR DAN KOMPENSASI TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASIONAL (STUDI PADA PNS DI LINGKUNGAN SETDA KOTA SEMARANG) (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study was to examine the effect of career development and organizational commitment and compensation for the performance of employees. The use of variable variables in the study refers to the results of previous studies. The research was conducted in the Secretariat of the city, as many as 102 respondents who used an employee,This study uses multiple regression analysis techniques. The research instrument used in this study qualify the validity and reliability. This study used two equation model is to determine the influence of career development and compensation to organizational commitment, and career development, compensation and organizational commitment to employee performance. The results showed that both models are able to significantly explain the dependent variable changes so that the model qualifies the goodness of fit.Hypothesis testing results indicate that career development and compensation a positive effect on organizational commitment. Similarly, compensation and career development and organizational commitment is also very significant influence on employee performance. The results also showed that organizational commitment was not berupakan factors that mediate the influence of career development and compensation to employee performance, but the factor of organizational commitment have tended to reinforce its influence on employee performance. Keywords: career development, compensation, organizational commitment, and employee performance